2018
DOI: 10.1007/s12011-018-1516-6
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic and Non-carcinogenic Risk Assessment of Heavy Metals in Groundwater Wells in Neyshabur Plain, Iran

Abstract: The present work reports the As, Cr, Cu, Pb, Zn, and Fe concentrations of drinking water samples in Neyshabur Plain, Iran. This study aimed also to ascertain the potential consumers' health risk of heavy metal intake. Heavy metal concentrations were analyzed by inductively coupled plasma optical emission spectrometry. The highest and lowest average values in the analyzed water samples were observed for Fe (9.78 ± 5.61 μg/L) and As (1.30 ± 2.99 μg/L), respectively. These values were well below the limits recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(92 citation statements)
references
References 44 publications
0
90
2
Order By: Relevance
“…The minimum limit of detection (LOD) for each heavy metal is resumed in Table 1. The proposed HPI was developed by assigning a rating or weightage (Wi) for each selected parameter [7,9,[13][14][15]. The rating is a value between zero and one, reflecting the relative importance of individual quality considerations, and can be defined as inversely proportional to the recommended standard (Si) for each parameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum limit of detection (LOD) for each heavy metal is resumed in Table 1. The proposed HPI was developed by assigning a rating or weightage (Wi) for each selected parameter [7,9,[13][14][15]. The rating is a value between zero and one, reflecting the relative importance of individual quality considerations, and can be defined as inversely proportional to the recommended standard (Si) for each parameter.…”
Section: Methodsmentioning
confidence: 99%
“…The desirable maximum value (Ii) indicates the standard limits for the same parameters in drinking water. The heavy metal pollution index is expressed by equation 1and (2) as follows [9,13]:…”
Section: Methodsmentioning
confidence: 99%
“…DAD can be used to estimate the amount of potential toxins absorbed by the human body through the dermal contact pathway, and its value represents the amount of chemical absorbed per unit of body weight, per day through the dermal contact pathway [16,17]. Its calculation formula is:…”
Section: Dermal Contact Pathwaymentioning
confidence: 99%
“…Groundwater quality is a major concern in both developed and developing nations [5]. Several studies from various parts of the world have highlighted the issue of deteriorating groundwater quality in Bangladesh [6], China [7], South Africa [8], Iran [9], Italy [10], Korea [11], Pakistan [12], and Thailand [13]. Some of these studies have also indicated public health issues arising out of human exposure to contaminated groundwater.…”
Section: Introductionmentioning
confidence: 99%